Intraocular pressure changes following intravitreal triamcinolone acetonide injection in steroid non-responder eyes - Aya Mohammed Saady; Heba Mohammed Fouad; Khaled Abdelgalil Mansour; Tamer Abdelrahem Mecky (Cairo : Aya Mohammed Saady, 2017)
Purpose: To investigatethe value of excludingIOP responders to topical prednisolone acetate eye drops beforeintravitreal triamcinolone acetonide (IVTA) injection in lowering the incidence of postinjection rise of IOP. Patients and methods:In this prospective comparative non-randomized study,patientsscheduled for IVTA in eyes with macular edema secondary to diabetic retinopathy, retinal vein occlusion, and post-cataract surgerywere assigned into 2 groups;Group A (Study): eyes with no IOP elevation following 4 weeks of prednisolone drops, and Group B (Control): eyesnot subjected to the pre-injection prednisolone drops test. Both groups had their IOP monitored for 4 weeks following IVTA. Results:Group A(study) included 32 eyes (Prednisolone test non-responders) in which 31.25% (10eyes) showed IOP elevation and 68.75% (22eyes) showed no IOP elevation, 4 weeks following IVTA.Group B(control) included 24 eyesin which54.2% (13 eyes) showed IOP elevation, and45.8% (11eyes)had no IOP elevation, 4 weeks following IVTA. The between group difference in the percentageof IOP elevations was statistically significantly lower in Group A(P value=0.006). Conclusion:The topical prednisolone eye drops provocative test appeared to significantly lower the rate of IOP elevation following IVTA injections
Thesis (M.Sc.) - Cairo University - Faculty of Medicine - Department of Ophthalmology
Issued also as CD
Keywords: Intraocular pressure; Intravitreal triamcinolone; Prednisolone acetate test